Family practice in the Eastern Mediterranean region primary health care for universal health coverage : in celebration of World Health Day 2019 (Boca Raton, FL : CRC Press, 2019)
This joint publication from the World Health Organization (WHO) and the World Organization of Family Doctors (WONCA) provides a concise analysis of the state of family practice in the 22 countries spread over North Africa, the Middle East and Western Asia, i.e. the Eastern Mediterranean Region (EMR) in both English and Arabic. It shares perspectives and advice from global and regional leaders on how family practice can be introduced and strengthened in high-, middle- and low-income countries.
OCLC-licensed vendor bibliographic record.
Keywords: Family medicine -- Practice -- Middle East; Family medicine -- Middle East; Primary care (Medicine) -- Middle East; Public-private sector cooperation -- Middle East; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; MEDICAL / Family & General Practice; MEDICAL / Public Health; MEDICAL / Administration